Combining microcosm biodegradation and reactive transport modeling to explore the feasibility of ATES-bioremediation approaches - Wienkenjohann, Henning; Bin Hudari, Mohammad Sufian; Mosthaf, Klaus; Vogt, Carsten; Nijenhuis, Ivonne; Rolle, Massimo (Frontiers in Water, 2025)
This study presents a process-based model analysis of non-isothermal biodegradation of chlorinated ethenes in batch microcosm setups and field-scale remediation, combining Aquifer Thermal Energy Storage with in situ bioremediation (ATES-ISB). The features of the proposed modeling framework include: (i) kinetic multi-phase mass transfer and temperature-dependent biodegradation in batch systems, and (ii) multi-dimensional non-isothermal fluid flow, heat transport, and contaminant transport in a physically and chemically heterogeneous aquifer combined with temperature-dependent microbial kinetics. The model was used to analyze an experimental microcosm dataset of temperature-dependent reductive dehalogenation of chlorinated ethenes, from which maximum specific degradation rates were derived. A scenario modeling investigation is presented, considering an ATES-ISB intervention in an aquifer contaminated with trichloroethene, where heated groundwater is injected and lactate is delivered to stimulate in situ microbial activity and contaminant transformation. Four scenario parameters were varied to identify the optimal conditions for efficient bioremediation. High lactate concentrations and temperatures at 20°C and 30°C led to more complete transformation of chlorinated ethenes in the considered heterogeneous aquifer system. Furthermore, the pumping rate and the natural groundwater flow velocity were found to control the delivery of heated water and solutes, including lactate, in the aquifer. The outcomes of the scenario simulations performed in this study are useful for designing non-isothermal bioremediation interventions in groundwater systems polluted with organic contaminants.